2007
DOI: 10.1128/iai.01963-06
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Stability and Trade-Off Effects of Pathoadaptive Mutations in the Escherichia coli FimH Adhesin

Abstract: FimH is the tip adhesin of mannose-specific type 1 fimbriae of Escherichia coli, which are critical to the pathogenesis of urinary tract infections. Point FimH mutations increasing monomannose (1M)-specific uroepithelial adhesion are commonly found in uropathogenic strains of E. coli. Here, we demonstrate the emergence of a mixed population of clonally identical E. coli strains in the urine of a patient with acute cystitis, where half of the isolates carried a glycine-to-arginine substitution at position 66 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 26 publications
4
34
1
Order By: Relevance
“…The occurrence of recent hotspot mutations is an indicator of genes evolving under positive selection (Chattopadhyay et al, 2009). Indeed, a single positively selected SNP leading to an amino acid replacement can promote adaptation to a new niche (Weissman et al, 2007). We detected an abundance of genes containing hotspot mutations and many were shared between the ST3 and ST36 ecotypes.…”
Section: Discussionmentioning
confidence: 86%
“…The occurrence of recent hotspot mutations is an indicator of genes evolving under positive selection (Chattopadhyay et al, 2009). Indeed, a single positively selected SNP leading to an amino acid replacement can promote adaptation to a new niche (Weissman et al, 2007). We detected an abundance of genes containing hotspot mutations and many were shared between the ST3 and ST36 ecotypes.…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, with a large collection of clinical isolates, we observed only few signs of patho-adaptive mutations in the UTI isolates and no correlation of T6N with UTI. Previous studies have suggested that the FimH mutations A48V, A62S and G66R affect the binding affinity of FimH and N70S in combination with S78N has been correlated to UTI isolates without effect on the binding affinity (Aprikian et al, 2007; Chen et al, 2009; Schwartz et al, 2013; Sokurenko et al, 1995; Weissman et al, 2007). We identified N70S/S78N in FimH significantly more often in UTI isolates compared to faecal isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The two forms of the lectin domain have important implications for binding and pathogenesis: the elongated conformation binds mannose with a significantly higher affinity than the compact form 126 . Residues that control these conformational transitions have been shown to be under positive selection, and pathoadaptive alleles of FimH have subsequently been identified 126128 . Thus, we now understand how protein–protein interactions and ligand binding can regulate a dynamic conformational equilibrium in the receptor-binding domain of FimH, and this is revealing unexpected insights into UTI pathogenesis and potentiating mannoside development.…”
Section: Treatment Of Urinary Tract Infectionsmentioning
confidence: 99%